Conception et réalisation sur PROTEUS d’un prototype de comptage d'énergie active - محمد رضا, مدلل; الهاشمي, منصور; عماد الدين, لصقع; حسام الدين, لعتري (University of El-Oued, 2022)
The energy meter, which has the role of calculating consumption as well as establishing the bill, is an essential element for electricity companies. The objective of the proposed studies is to develop (design, produce) new types of Active energy measurement systems for single-phase energy consumers. يعد عداد الطاقة الذي له دور في حساب استهلاك الطاقة وكذلك إنشاء الفاتورة ، عنصرا اساسيا لشركات الكهرباء . الهدف من الدراسات المقترحة هو تطوير (تصميم وإنتاج ) أنواع جديدة من أنظمة قياس الطاقة النشيطة لمستهلكي الطاقة احادي الطور
مذكرة ماستر تخصص كهروميكانيك
Keywords: Active energy, shunt sensor, RMS, C programming, DSPIC microcontroller; الطاقة النشيطة ، مستشعر التحويل ، RMS ، برمجة c ، المتحكم dspic